Numerical Algorithms for Calculating Temperature, Layered Stress, and Critical Current of Overhead Conductors. (30th April 2020) - Liu, Yongdou; Chen, Zhiwei; Gu, Quan
Abstract : Accurate calculation of temperature, stress, sag, and critical current (corresponding to critical temperature) of operational overhead conductors is important for ensuring the strength and sag safety of overhead lines. Based on 2D steady-state heat transfer equations, this article studies the temperature fields of the cross section of typical electrified conductors and establishes numerical simulation methods for calculating the layered stress, sag, and critical temperature. Using the algorithm, the relationship between the critical temperature and characteristics of conductors (e.g., the sag and tensile force) is studied. The results are verified by a comparison with the test results for heat-resistant aluminum alloy conductors JNRLH1/G1A-400/65 and JNRLH1/G1A-630/55. Finally, the paper studies the relationship between the critical temperature of the conductor and its most sensitive factors.